Development of a Mg-Based Alloy with a Hydrogen-Storage Capacity of 7 wt% by Adding a Polymer CMC via Transformation-Involving Milling - Song, Myoung Youp; Choi, Eunho; Kwak, Young Jun (Korean Journal of Metals and Materials, 2018)
The addition of CMC (Carboxymethylcellulose, Sodium Salt) may improve the hydriding and dehydriding properties of Mg since it has a relatively low melting point and the melting of CMC during transformation-involving milling may put the milled samples in good states to absorb and release hydrogen rapidly. Samples with compositions of 95 wt% Mg + 5 wt% CMC (named Mg-5CMC) and 90 wt% Mg + 10 wt% CMC (named Mg-10CMC) were made using transformation-involving milling. Mg-5CMC was activated in about 3 hydriding-dehydriding cycles. After activation, Mg-5CMC had a larger amount of hydrogen absorbed in 60 min, Ha (60 min), than Mg-10CMC and milled Mg. At the fourth cycle (CN=4), Mg-5CMC had a very high beginning hydriding rate (1.45 wt% H/min) and Ha (60 min) (7.38 wt% H), showing that the activated Mg-5CMC has an effective hydrogen-storage capacity of about 7.4 wt% at 593 K in hydrogen of 12 bar at CN=4. Mg-5CMC after transformation-involving milling contained Mg and very small amounts of β- MgH2 and MgO, and Mg-5CMC dehydrogenated at 593 K in hydrogen of 1.0 bar at the 4th cycle contained Mg and tiny amounts of β-MgH2 and MgO, with no evidence of the phases related to CMC. The milling of Mg with CMC in hydrogen is believed to introduce defects and cracks and lessen the particle size. To the best of our knowledge, this study is the first in which a polymer CMC is added to Mg by transformation-involving milling to improve the hydriding and dehydriding properties of Mg. KCI Citation Count: 15